1996
DOI: 10.1099/00222615-45-4-263
|View full text |Cite
|
Sign up to set email alerts
|

A particle agglutination assay for rapid identification of heparin binding to coagulase-negative staphylococci

Abstract: The heparin-binding properties of six different species of coagulase-negative staphylococci were examined by a particle agglutination assay. Heparin (mol. wt 4000-6000), mildly treated with sodium periodate, was covalently coupled to amino-modified latex beads (0.72 p m diameter). The particle agglutination assay was validated by comparing results with the adhesion (percentage binding of adherent cells) of coagulase-negative staphylococcal strains to heparinised microtitration plates. Of 38 different coagulase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Consistent with this hypothesis, several groups have evidence suggesting that S. aureus codes for a heparin binding protein (14,16,37). Pascu and colleagues found that 30 of 38 coagulase-negative staphylococci were able to aggregate to heparin-coated beads and this binding was inhibited by several sulfated molecules (48). Another report showed the presence of heparin binding proteins on the surface of Neisseria gonorrhoeae, Helicobacter pylori, S. epidermidis, S. aureus, Staphylococcus pyogenes, and two species of Yersinia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, several groups have evidence suggesting that S. aureus codes for a heparin binding protein (14,16,37). Pascu and colleagues found that 30 of 38 coagulase-negative staphylococci were able to aggregate to heparin-coated beads and this binding was inhibited by several sulfated molecules (48). Another report showed the presence of heparin binding proteins on the surface of Neisseria gonorrhoeae, Helicobacter pylori, S. epidermidis, S. aureus, Staphylococcus pyogenes, and two species of Yersinia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Out of \ 400 Lactobacillus strains, the 40 strains expressing the highest binding of porcine mucin were selected for further testing. Mucin binding was repeated with bovine submaxillary gland mucin and porcine type II mucin (Sigma) in a particle agglutination assay (PAA) (6).…”
Section: Adhesi×e Mechanismsmentioning
confidence: 99%
“…Binding of human bronectin (Fn) (8), collagen type I and III (Collagen Research, Palo Alto, CA, USA), vitronectin (Vn) (9), brinogen (Imco, Stockholm, Sweden, heparin (Fluka Chemie AG, Heidelberg, Germany) and fetuin (Sigma Chemical Co.) was studied in immobilized form at neutral pH and at 3.5 (6).…”
Section: Adhesi×e Mechanismsmentioning
confidence: 99%
“…S. saprophyticus strain TW 111, isolated from a patient with urinary tract infection and previously shown by agglutination assay [9] not to bind heparin was included as a negative control. CNS strains isolated from healthy carriers were also included.…”
Section: Chemicalsmentioning
confidence: 99%
“…wts of 66 and 60 kDa, respectively, were earlier identi®ed as binding heparan sulphate (HS) and heparin [7]. Also, CNS may interact with heparin and HS, as shown for whole staphylococcal cells which bound avidly to heparinised polymer surfaces [8], or to heparin immobilised on latex particles [9]. The ability of both S. aureus and CNS strains to bind the heparin-binding growth factors, basic ®broblast growth factor (bFGF) and platelet-derived growth factor (PDGF) has also been shown [10].…”
Section: Introductionmentioning
confidence: 99%